Compression of Open-Cell Aluminium - KASZA, Piotr; LIPOWSKA, Barbara; PĘCHERSKI, Ryszard Bolesław; STRĘK, Anna Małgorzata; WAŃCZYK, Krzysztof (Engineering Transactions, 2016)
The paper presents compression test results of self-made open-cell aluminium which was produced by the investment casting method. Two groups of samples were studied: prototype samples containing some structural imperfections (apparent density 0.485 g/cm3) and regular samples without visible mistakes (app. density 0.312 g/cm3). Performed experimental research covered quasi-static compression tests with one hysteresis loop. Based on experimental results, new measures to help material characterisation were proposed: instant and average loop secant gradients (E_inst.sec^** and E_av.inst.sec^**) and average linear loop gradient (E_av.lin^**).